Hypoxia-Response Plasmid Vector Producing bcl-2 shRNA Enhances the Apoptotic Cell Death of Mouse Rectum Carcinoma - Takashi Fujioka; Naoya Matsunaga; Hiroyuki Okazaki; Satoru Koyanagi; Shigehiro Ohdo (Elsevier, 2010)
Hypoxia-induced gene expression frequently occurs in malignant solid tumors because they often have hypoxic areas in which circulation is compromised due to structurally disorganized blood vessels. Hypoxia-response elements (HREs) are responsible for activating gene transcription in response to hypoxia. In this study, we constructed a hypoxia-response plasmid vector producing short hairpin RNA (shRNA) against B-cell leukemia/lymphoma-2 (bcl-2), an anti-apoptotic factor. The hypoxia-response promoter was made by inserting tandem repeats of HREs upstream of cytomegalovirus (CMV) promoter (HRE-CMV). HRE-CMV shbcl-2 vector consisted of bcl-2 shRNA under the control of HRE-CMV promoter. In hypoxic mouse rectum carcinoma cells (colon-26), the production of bcl-2 shRNA driven by HRE-CMV promoter was approximately 2-fold greater than that driven by CMV promoter. A single intratumoral (i.t.) injection of 40 μg HRE-CMV shbcl-2 to colon-26 tumor-bearing mice caused apoptotic cell death, and repetitive treatment with HRE-CMV shbcl-2 (40 μg/mouse, i.t.) also significantly suppressed the growth of colon-26 tumor cells implanted in mice. Apoptotic and anti-tumor effects were not observed in tumor-bearing mice treated with CMV shbcl-2. These results reveal the ability of HRE-CMV shbcl-2 vector to suppress the expression of bcl-2 in hypoxic tumor cells and suggest the usefulness of our constructed hypoxia-response plasmid vector to treat malignant tumors.[Supplementary Figures: available only at http://dx.doi.org/10.1254/jphs.10054FP] Keywords:: hypoxia, hypoxia inducible factor 1 (HIF-1), hypoxia-response element (HRE), short hairpin RNA (shRNA), B-cell leukemia/lymphoma-2 (bcl-2)